BISNIS KELUARGA MANGKUNEGARAN - Birsyada, Muhammad Iqbal; Wasino, Wasino; Suyahmo, Suyahmo; Joebagio, Hermanu (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2016)
The history of economic development of Javanese community has experienced a very unique dynamic. In the XV and XVI centuries, trading tradition has been done by Javanese community along the north coastal of Java. But, the trading tradition getting dimmer in line with the strategy of economic centralization carried out by Sultan Agung prohibiting the people to trade in foreign countries. In the XIX century, that’s econdition is change, Mangkunegara IV restore the entrepreneurial tradition through various strategies. In addition, to restoring the entrepreneurial tradition of Javanese society, Mangkunegara IV also broke the old tradition of kepriyayinan (Javanese aristocrate) to want to do business, not just live in pleasure as breeds nobility or gentry class. Therefore, reviewing to the business strategy of Mangkunegaran IV becomes important, as part of the history of economic development Javanese community. By using the historical method and a multidimensional approach, through a variety of primary sources such as Mangkunegara IV literature, the study found that the Mangkunegaran IV’s business strategy conducted by building a centers of sugar cane farm and modernization of sugar factories on a large scale, so as to obtain additional revenue for the Mangkunegaran IV family. The successfull of his business, demonstrates to the Javanese nobility that he was a king who had a strong entrepreneurial spirit.***Sejarah perkembangan ekonomi masyarakat Jawa mengalami dinamika yang sangat unik. Pada abad XV dan XVI, tradisi berdagang telah dilakukan oeh masyarakat Jawa di sepanjang pantai utara Jawa. Akan tetapi tradisi tersebut semakin meredup seiring adanya strategi sentralisasi ekonomi yang dilakukan oleh Sultan Agung yang melarang rakyatnya berdagang ke manca negara. Pada abad XIX, Mangkunegara IV mengembalikan tradisi wirausahawan tersebut melalui berbagai strategi. Selain itu, Mangkunegara IV juga mendobrak tradisi “kolot kepriyayinan” Jawa agar mau melakukan bisnis, bukan hanya hidup dalam kesenangan sebagai trah bangsawan. Karena itu, mengkaji strategi bisnis keluarga Mangkunegaran IV menjadi penting, sebagai bagian dari sejarah perkembangan ekonomi masyarakat Jawa. Dengan metode penelitian sejarah dan pendekatan multidimensional, melalui berbagai sumber primer seperti karya-karya sastra Mangkunegara IV, penelitian ini menemukan bahwa strategi bisnis keluarga Mangkunegaran IV dilakukan dengan membangun pusat-pusat perkebunan tebu dan modernisasi pabrik gula secara besar-besaran, sehingga memperoleh pendapatan tambahan bagi praja. Kesuksesan bisnis ini menunjukkan kepada para bangsawan Jawa bahwa dia adalah seorang raja yang memiliki jiwa entrepreneurship yang kuat.